The endothelial nitric oxide synthase Glu298Asp polymorphism is not a risk factor for endometriosis in south Indian women. - Bhanoori, M; Kameshwari, D; Zondervan, K; Deenadayal, M; Kennedy, S; Shivaji, S (2008)
OBJECTIVE: To investigate whether the eNOS gene influences the risk of developing endometriosis in south Indian women. STUDY DESIGN: The single nucleotide polymorphism, Glu298Asp, in exon7 of the eNOS gene was tested for association in a case-control study of 232 affected women and 210 women with no evidence of disease. All the women were infertile, ascertained from the same infertility clinic. The genotype frequencies of the polymorphism were compared, using polymerase chain reaction and sequencing analysis. The localization and expression of eNOS in the eutopic endometrium of five cases and four controls was also analyzed using immunohistochemistry and western blotting. RESULTS: No statistically significant differences were observed in the genotype distributions and allele frequencies (p=0.3) between the cases and controls according to codominant, dominant and recessive genotype models. The localization and expression of this protein were similar in the endometrium of cases and controls. CONCLUSION: In the present study we could neither observe a difference in the eNOS expression nor establish an association between the eNOS Glu298Asp exon 7 polymorphism in south Indian women with endometriosis.